(untitled) (Research, Society and Development, 2020)
In this article we present, in the form of a metatext, some facts that circulate among certain members of the collective that works with chemistry teaching-learning from the perspective of the history and philosophy of science, aiming to give theoretical support to new science teaching proposals, notably those of chemistry. For this we base ourselves on the epistemology of Ludwik Fleck, especially in his epistemological category Style of Thought. We take as starting point the analysis of certain articles published in three scientific journals. The study was conducted from a framework that sought to look at the issues discussed by the authors in the manuscripts analyzed, starting with a non-disciplinary approach. As the first results are presented, in the still chaotic form of a metatext, the assertions that support the discourses of a possible Style of Thought that unites those researchers. For theoretical support of the proposal we bring some pressing discussions in the field of History and Philosophy of Science from a socio-historical approach to science in line with the precepts of Fleck’s epistemology.